Thrombospondin-1/CD47 Interaction Regulates Th17 and Treg Differentiation in Psoriasis - Rodríguez-Jiménez, Pedro; Chicharro, Pablo; Llamas-Velasco, Mar; Cibrian, Danay; Trigo-Torres, Laura; Vara, Alicia; Jiménez-Fernández, María; Sevilla-Montero, Javier; Calzada, Maria J.; Sánchez-Madrid, Francisco; de la Fuente, Hortensia; Daudén, Esteban (Frontiers in Immunology, 2019)
Accumulating evidence on the role of Thrombospondin-1 (TSP-1) in the immune response has emerged during the last years. In spite of the importance of TSP-1 not only as anti-angiogenic factor but also as an immunomodulatory molecule, studies on the role of TSP-1 in psoriasis have been neglected. TSP-1 and CD47 expression were analyzed in skin samples from psoriasis patients and control subjects using RT-PCR and immunofluorescence. Expression of these molecules was also evaluated in peripheral blood CD4+ T cells, moDCs and circulating primary DCs. The functional role of TSP-1/CD47 signaling axis in psoriasis was assessed in Th17 and Treg differentiation assays. Additionally, small interfering RNA assays specific to TSP-1 were performed in CD4+ T cells and monocyte derived DC to specifically evaluate the function of this protein. Lesional skin of psoriasis patients expressed lower TSP-1 and CD47 mRNA levels compared to non-lesional skin or skin from controls. Immunofluorescence staining revealed decreased expression of CD47 in CD45+ dermal cells from psoriasis samples compared to control subjects. Peripheral CD4+ T cells and circulating primary DCs from psoriasis also expressed lower levels of CD47 compared to controls. Although no significant differences were detected in TSP-1 expression in CD4+ T cells and moDCs between patients and controls, TSP-1 expression in psoriasis patients inversely correlated with disease activity evaluated by the Psoriasis Area and Index Activity. Furthermore, exogenous TSP-1 inhibited Th17 differentiation and stimulated the differentiation of CD4+ T cells towards Treg cells. Furthermore, RNA interference specific for TSP-1 confirmed the role of this molecule as a negative regulator of T cell activation. Because of the impact of TSP-1/CD47 signaling axis in Th17 and Treg differentiation, a dysregulated expression of these molecules in the immune cells from psoriasis patients may favor the exacerbated inflammatory response in this disease.